PENGARUH UKURAN PERUSAHAAN, ROA DAN LEVERAGE PADA TARIF PAJAK EFEKTIF PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA 2017-2020 (SUBSEKTOR CONSUMER GOODS) - Krisnawati Tarigan; Andrew Liejaya Octavianus (Jurnal Akuntansi, 2022)
The study aims to test whether Company Size, Return on Asset, and Leverage affect Effective Tax Rates. The data used is secondary data or derived from the financial statements of manufacturing companies registered with the IDX for the period 2017-2020. Retrieval techniques use purposive sampling techniques. The number of samples processed is 32 companies with overall observation data reaching 128 samples. The data was analyzed using multiple linear regression analysis and processed using the SPSS version 24 program. The results showed that the Size of the Company had a positive but insignificant effect on the effective tax rate, the return on asset negatively and significantly on the effective tax rate, and the leverage had a significant positive effect on the effective tax rate. Keywords: Company Size, Return on Asset, Leverage, Effective Tax Rate.